Caracterizacion del hibrido 1831 X UDG 110 de sorgo (Sorghum bicolor (L.) Moench) - Pedrroso Perez, R.=700 1 Rodriguez Fuentes, C.; Martin Fagundo, D.; Saucedo Castillo, O.
(En, Es)
ilus., 9 ref.
Keywords: SORGOS; RENDIMIENTO DE CULTIVOS; GRANOS; CUBA